WILGA Photonics and Web Engineering 2010 - Romaniuk, Ryszard S. (Photonics Letters of Poland, 2010)
SPIE - PSP WILGA Symposium is convened twice a year in January and in May, gathering new adepts of advanced photonic and electronic systems. The event is oriented towards components and applications. WILGA Symposium on Photonics and Web Engineering is well known in the web for its devotion to "young research" promotion under the eminent sponsorship of international engineering associations like SPIE and IEEE and their Poland Sections or Counterparts. WILGA is supported by the most important national professional organizations like KEiT PAN and PSP - Photonics Society of Poland. Apart from young researchers Wilga Symposium is always regularly attended by students' mentors. Full Text: PDF References: Wilga2002?Proc.SPIE 5125 Wilga2003?Proc.SPIE 5484 Wilga2004?Proc.SPIE 5775 Wilga2005bis?Proc.SPIE 5948 Wilga2005?Proc SPIE 6159 Wilga2006?Proc.SPIE 6347 Wilga2007?Proc.SPIE 6937 Wilga2008?Proc.SPIE 7124 Wilga2009?Proc.SPIE 7502 Wilga2010?Proc.SPIE 7376 WILGA web page: http://wilga.ise.pw.edu.pl WILGA WIKI: http://pl.wikipedia.org/wiki/SympozjumWilga